A new species of Aoruroides Travassos & Kloss, 1958 (Nematoda: xyuridomorpha: Thelastomatidae) parasite of the wood-burrowing cockroach Panesthia angustipennis spadica (Shiraki, 1906) (Blattodea: Blaberidae: Panesthiinae) from Japan with comments on the validity of the genus Aoruroides - Morffe, Jans; García, Nayla; Hasegawa, Koichi; Carreno, Ramon A. (Zootaxa, 2019)
Aoruroides chubudaigaku n. sp. (Nematoda: Oxyuridomorpha: Thelastomatidae) is described from the wood-burrowing cockroach Panesthia angustipennis spadica (Shiraki, 1906) (Blattodea: Blaberidae: Panesthiinae) from Aichi prefecture, Japan. Females of A. chubudaigaku n. sp. are similar to A. costaricensis Carreno & Tuhela, 2011 by the position of the nerve ring at level of the first third of the isthmus, the body length and the comparative measurements of the oesophagus and tail. They differ by the position of the excretory pore and the vulva. The males of A. chubudaigaku n. sp. are characterized by the absence of ornamentations in the cervical cuticle and the nerve ring located at the posterior third of the corpus. In addition, the males of the new species can be differentiated by the length of the body and the comparative lengths of the oesophagus and the tail. The phylogeny of A. chubudaigaku n. sp. is inferred by the D2-D3 domains of the LSU rDNA and the validity of the genus Aoruroides Travassos & Kloss, 1958 is discussed on the basis of both molecular and morphological data. This constitutes the first species of the genus Aoruroides described from the Japanese archipelago.